Toussaint Louverture papers - Toussaint Louverture, 1743-1803.
Correspondence, proclamations, decrees, and passport relating to Toussaint Louverture's efforts to establish Haiti as a black-governed French protectorate.
In part, positive and negative photocopies and handwritten transcripts.
Reformer, Haitian army officer, and public official. Full name: Pierre Dominique Toussaint Louverture.
Collection material in French, with English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Haiti -- History -- Revolution, 1791-1804.; Haiti -- History -- 1804-1844.; Army officers, Haitian; Public officials -- Haiti; Reformers